SELF-ACTUALISATION AND COMPUTER SELF-EFFICACY AMONG THE PROFESSIONAL COURSES ACADEMICIANS: A CORRELATIONAL STUDY - Siddiqui, Hureen Wasifa; Sunanda, G. Mary (Indonesian Journal of Educational Development (IJED), 2024)
The spreading use of technology will have repercussions on individuals’ Self-understanding and their belief in themselves concerning technology. Psychologists have studied these two major phenomena under the title Self-actualisation and Computer Self-efficacy. Multiple papers have been published on Self-actualisation and Computer Self-efficacy but minimum research has been explored concerning the association between Self-actualisation and Computer Self-efficacy. This paper is a maiden effort to study the association of Self-actualisation and Computer Self-efficacy among academicians of professional courses. An online and offline survey was carried out where the Self-actualisation Scale prepared by Kaufman (2018) and the Computer Self Efficacy Questionnaire curated by Teo & Ling Koh (2010) was administered to the participants. The data was analysed using mean, standard deviation, standard error, and Pearson’s Product Moment Correlation. The results supported the preposition of a previous study, which suggested a relationship between technical competency and self-actualisation by placing technical competency under D-needs and Self-actualisation under B-needs of Maslow’s hierarchy of needs. Further exploration of the outcome was done concerning academicians followed by educational implications.